2021
DOI: 10.1038/s41598-021-92245-5
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding outcomes and factor utilization after switching to an extended half-life product for prophylaxis in haemophilia A in Austria

Abstract: To prevent bleeding in severe haemophilia A [SHA, defined as factor VIII (FVIII) activity < 1%] regular prophylactic FVIII replacement therapy is required, and the benefits of factor products with extended half-life (EHL) over traditional standard half-life (SHL) are still being debated. We performed a multi-centre, retrospective cohort study of persons with SHA in Austria aiming to compare clinical outcomes and factor utilization in patients with SHA, who switched from prophylaxis with SHL to an EHL. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 31 publications
1
23
0
3
Order By: Relevance
“…Among the 46 identified publications, 38 were only available as abstracts, 11–48 and eight were published as full articles 49–56 . The two publications by Van der Sluijs et al 36,55 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 46 identified publications, 38 were only available as abstracts, 11–48 and eight were published as full articles 49–56 . The two publications by Van der Sluijs et al 36,55 .…”
Section: Resultsmentioning
confidence: 99%
“…Thirty three of the identified publications did not specify whether the study population included children, adolescents or adults 11–13,15–22,25,26,30,31,33–37,39,41–48,53–56 . Of the remaining, three publications only included children, 32,40,51 one publication only included adolescents, 14 three publications only included adults, 38,49,52 and six publications included a combination of children, adolescents and adults 23,24,27–29,50 . Most publications included previously treated patients 11–14,17–19,22–25,27,28,30–37,41–43,45,46,48–55 and patients with severe haemophilia A 11,14,15,17,18,20–23,25–27,29,31,33–35,40,41,43,45–47,49–54,56 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of maintaining FVIII within a specified range to allow for safe antiplatelet/anticoagulant therapy underlines how the use of molecules with a more stable pharmacokinetic profile might be of help, allowing to maintain higher trough levels for longer without the need for very high peaks that could increase the risk of thrombosis in subjects with pre‐existing CV risk factors. For example, EHL products have a half‐life approximately 1.4–1.6 times greater than standard half‐life products and offer the potential to reduce prophylactic infusion frequency and/or provide higher trough levels 35 …”
Section: Discussionmentioning
confidence: 99%
“…For example, EHL products have a half-life approximately 1.4-1.6 times greater than standard halflife products and offer the potential to reduce prophylactic infusion frequency and/or provide higher trough levels. 35 Not only is the impact of haemophilia and its treatment on CVD not fully understood, it is also too soon to assess how the risk of CVD will affect PWH who are treated with non-replacement therapy (i.e., emicizumab) or gene therapy. Evaluating the CV risk in PWH is complex and standard risk equations may not apply; for example, a 5-year prospective study in 709 male PWHA aged ≥30 (all severities) concluded that PWH have a lower-than-predicted incidence of CVD and that the QRISK-2011 risk predictor is not valid for PWH.…”
Section: Pwha Receiving Replacement Therapy and For Whom Anticoagulat...mentioning
confidence: 99%